ANALISIS PENGARUH LEVERAGE OPERASI, PERTUMBUHAN ASET DAN PROFITABILITAS TERHADAP STRUKTUR MODAL STUDI KASUS PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BEI - M. Shofiyuddin (Jurnal Ekonomi Dan Bisnis, 2016)
he purpose of this research is to examine the influence DOL ( Debt of Leverage ), Growth, NPM, DFL,toward DER. The research sample  are 8 Food and Beverages, it was done by using purposive samplingmethod with criteria food and Beverages is always who presenting and submitted annual report. Dataanalysis with multi linear regression and hypothesis test used F- statistic and t-statistic, testdeterminant at level of significance 5%, a classic assumption examination which consist of data,normality  tes, multicolinerity test, heteroskedasticity test and autocorrelation test is also being doneto test the`hypothesis the result of this research showed that F-statistic, independent variable DOL,Growth, NPM, DFL have significance influence on DER, than the  result of this research showed that t-Statistic .independent variable DOL, Growth and DFL have nosignificant influence on DER at level ofsignificant more than 5%, but variable NPM have significant influence on DER at level of significantless than 5%.Prediction capability from these four variable toward DER is 62,5%, where the balanced37,5% is affected to other factor which was not to be entered to research model. Keyword : Growth, NPM, DFL, toward  DER